The Roadmap to a Sustainable Artisanal and Small-Scale Mining (ASM) in Ghana - Bansah, J. K. (H. : ĐHKT, 2020)
The Ghanaian artisanal small-scale mining (ASM) industry is well over 2,000 years old. No precise ASM employment data can be found for Ghana, although it is estimated that some 1,000,000 people are involved directly or indirectly in the extraction of gold and diamonds and thus about 60 per cent of the country’s mining labour force is employed at small-scale mines. In 1989, the Small Scale Gold Mining Law was introduced to help in improving the ASM activities and minimize associated environmental hazards. However, the sector continues to face significant environmental, safety, health and security challenges. These challenges have largely been attributed to lack of involvement of professionals, such as, mining, environmental and safety, geological and geomatics engineers and their linkage with existing state institutions. The absence of trained engineers in the ASM and proper interactions with state institutions is believed to have contributed to poor safety standards, lack of environmental protection, and poor choice of mining methods, resulting in fatalities, damage to the environment, and significant ore losses. This study evaluates the diverse contributions that each of the above mentioned professionals can actively play to ensure the sustainability of the ASM sector. We (a team of professionals from the University of Mines and Technology) have already toured Ghana-wide to all the ASM districts and engaged with the various stake holders, as part of the government’s effort to streamline the sector and have highlighted the following key areas to be strengthened to ensure that the above objective could be achieved: improving productivity through training, diversification of the sector and appropriate technology transfer. Next, is how well the above could be implemented and this has called for developing a roadmap for proper execution.